Bridging regulation theory and heterodox economics for effective industrial policy delivery: a theoretical exploration - Cunha, Bruno Queiroz (Revista do Serviço Público, 2025)
Regulation theory has long relied on the lexicon of “regulatory reform” to promote static economic efficiency and disciplined and rigid governance models. Although numerous authors have pointed to the technocratic nature of the existing ‘regulatory orthodoxy’ and stressed the need to incorporate non-economic values in regulatory decision-making to improve its democratic component, contemporary critiques fall short of repositioning regulation on a more progressive economic basis. This article delves into this epistemic gap by drawing on theoretical contributions from interdisciplinary research streams attuned to heterodox economic thinking. We critique the ‘regulatory orthodoxy’ at both substantive and procedural levels, outlining new macro-, meso-, and micro-level regulatory parameters. Ultimately, we provide insights into how a regulatory heterodoxy can enhance theory and practice for effective industrial policy delivery.